Neutrophil extracellular traps form predominantly during the organizing stage of human venous thromboembolism development. (June 2014) - Savchenko, A. S.; Martinod, K.; Seidman, M. A.; Wong, S. L.; Borissoff, J. I.; Piazza, G.; Libby, P.; Goldhaber, S. Z.; Mitchell, R. N.; Wagner, D. D.
Summary Background A growing health problem, venous thromboembolism (VTE), including pulmonary embolism (PE) and deep vein thrombosis (DVT), requires refined diagnostic and therapeutic approaches. Neutrophils contribute to thrombus initiation and development in experimental DVT. Recent animal studies recognized neutrophil extracellular traps (NETs) as an important scaffold supporting thrombus stability. However, the hypothesis that human venous thrombi involve NETs has not undergone rigorous testing. Objective To explore the cellular composition and the presence of NETs within human venous thrombi at different stages of development. Patients and Methods We examined 16 thrombi obtained from 11 patients during surgery or at autopsy using histomorphological, immunohistochemical and immunofluorescence analyses. Results We classified thrombus regions as unorganized, organizing and organized according to their morphological characteristics. We then evaluated them, focusing on neutrophil and platelet deposition as well as micro‐vascularization of the thrombus body. We observed evidence of NET accumulation, including the presence of citrullinated histone H3 (H3Cit)‐positive cells. NETs, defined as extracellular diffuse H3Cit areas associated with myeloperoxidase and DNA, localized predominantly during the phase of organization in human venous thrombi. Conclusions NETs are present in organizing thrombi in patients with VTE. They are associated with thrombus maturation in humans. Dissolution of NETs might thus facilitate thrombolysis. This finding provides new insights into the clinical development and pathology of thrombosis and provides new perspectives for therapeutic advances.